2016
DOI: 10.3389/fnhum.2015.00711
|View full text |Cite
|
Sign up to set email alerts
|

Age-Sensitive Effects of Enduring Work with Alternating Cognitive and Physical Load. A Study Applying Mobile EEG in a Real Life Working Scenario

Abstract: Ergonomic assessment of a workplace requires the evaluation of physical as well as cognitive aspects of a particular working situation. In particular the latter is hardly possible without interfering in the natural setting. Mobile acquisition of neurophysiological measures (such as parameters of the EEG) may close this gap. At a simulated workplace we tracked older and younger participants with mobile EEG during a 4–5 h work shift. They had to perform either a monotonous cognitive task, a self-paced cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 54 publications
2
34
0
1
Order By: Relevance
“…Taken together, psychological strain in the PCL was higher for the young men than for the elderly men. This is consistent with a study by Wascher et al (2016) that found young people experienced more fatigue from monotonous cognitive exercise than the elderly. Thus, impairment of the intrinsic motivation of young people could be a key factor in why young people felt a greater psychological fatigue because it has been clearly established that when the subjects are involved in mental activity and engage with it, they experience less mental fatigue ( Shigihara et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, psychological strain in the PCL was higher for the young men than for the elderly men. This is consistent with a study by Wascher et al (2016) that found young people experienced more fatigue from monotonous cognitive exercise than the elderly. Thus, impairment of the intrinsic motivation of young people could be a key factor in why young people felt a greater psychological fatigue because it has been clearly established that when the subjects are involved in mental activity and engage with it, they experience less mental fatigue ( Shigihara et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in the last few years there has been a steady growth in the number of studies successfully employing mobile EEG to query aspects of cognitive function in real world contexts (e.g., Gramann et al, 2010;Wascher et al, 2014Wascher et al, , 2016Jungnickel & Gramann, 2016), including ERPs associated with attention (Debener et al, 2012;De Vos et al, 2014;Zink et al, 2016). Most relevant here, mobile EEG has been employed to investigate the influence of real world environments on the formation of episodic memories (Griffiths et al, 2016), providing a clear demonstration that memory-related EEG data can be reliably obtained in naturalistic settings.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…AMS is an inexpensive psychophysiological assessment, suitable for administration in outpatient‐clinical settings, and could be examined longitudinally in veterans in order to determine whether increased startle during unpleasant pictures is a trait and/or state indicator of suicide risk. Recent mobile EEG work showed results comparable to laboratory studies and sufficient validity and reliability of data, providing support for the concept of recording AMS in the clinic (Wascher et al, ).…”
Section: Discussionmentioning
confidence: 78%